Facilities management business opportunities - Milala, Sani Inusa; Md Ariffin, Khadijah; Kasim, Rozilah (Penerbit UTHM, 2022)
Facilities management is a profession that has an enormous scope of business opportunities; facility management (FM) has become one of the fastest-growing sectors in the recent decade. On the other hand, FM's scope and identity is a heterogeneous field of work that involves a wide range of tasks, responsibilities, and knowledge. The aim of this study is to explore the facilities management business opportunities; the study employed a systematic and intensive literature review to achieve the aim of the study. 93 numbers journals related to the subject study was collected and screened 50 numbers of the journal and 30 was used. The journals were collected from 3 search databases the science direct, Scopus and emerald. From the previous kinds of literature reviewed, it was found that there are numerous facilities management business opportunities, including maintenance, as a result of increases in the construction in our cities. There are numerous studies carried out on the facilities management and its scope of functions, a better understanding of the scope of the facilities management give a hint to several business opportunities that can retrofit the modern world. In the various aspects of human endeavors, it was confirmed in the previous studies that facilities management is necessary for integrating the other aspect of the system to work in coordination. And from the study's findings, it also shown that Due to the day-by-day usage of the facilities, we have the revenues we generated and the time we have will not allow us to renew the facilities, it takes an extended period, some feature of the facilities denies such, going with this, the maintenance role of facilities management business is thereby played.it is concluded that facilities management has numerous roles to play, and facilities management business opportunities go with the dynamism of the technological development of the globe.